(untitled) (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to determine the effect of the use of ethnomathematics-based Student Worksheets (LKPD) with the context of traditional roofs on the numeracy skills of eighth-grade students of Karuni Christian Middle School. The study used a quantitative approach with a pre-experimental method through the *One Group Pretest–Posttest Design*. The research subjects consisted of 23 eighth-grade students who participated in learning about triangles and trapezoids. Data were collected through numeracy ability tests, observation, and documentation. Data analysis was carried out using descriptive statistics, the Shapiro–Wilk normality test, the Wilcoxon Signed Rank Test, and N-Gain analysis with the help of SPSS 16.0. The results showed that the average student numeracy score increased from 62.30 in the pretest to 94.13 in the posttest. The Wilcoxon test results showed a significance value of 0.000 (<0.05), which indicated a significant increase in numeracy skills after the use of LKPD. In addition, the N-Gain value of 0.81 is included in the high category. These findings indicate that ethnomathematics-based LKPD is able to help students understand mathematical concepts more contextually by linking the material to local culture, so that learning becomes more meaningful and contributes to improving students’ numeracy skills